Adaptation of model genetically engineered microorganisms to lake water: growth rate enhancements and plasmid loss. - Sobecky, P A (1992)
When a genetically engineered microorganism (GEM) is released into a natural ecosystem, its survival, and hence its potential environmental impact, depends on its genetic stability and potential for growth under highly oligotrophic conditions. In this study, we compared plasmid stability and potential for growth on low concentrations of organic nutrients of strains of Pseudomonas putida serving as model GEMs. Plasmid-free and plasmid-bearing (NAH7) prototrophic isogenic strains and two amino-acid auxotrophs, all containing antibiotic resistance markers, were held physically separate from but in chemical contact with lake water containing the natural bacterium-sized microbial populations. Cells were reisolated at intervals over a 2-month period to determine the percent retaining the plasmid and the specific growth rate on various media. Plasmid stability in lake water was strongly strain specific; the NAH7 plasmid was stably maintained by the prototrophic strain for the duration of the test but was lost within 24 h by both of the auxotrophs. Specific growth rates of reisolates, compared with those of the corresponding non-lake water-exposed strains (i.e., parental strains), were not different when measured in rich medium (Luria-Bertani broth). However, specific growth rates were 42, 55, and 63% higher in reisolates of auxotrophs and the plasmid-free prototroph, respectively, when measured in 10-fold-diluted medium after exposure of 15 days or longer to lake water. Moreover, lake water-exposed strains grew actively when reintroduced into sterile lake water (28- to 33-fold increase in numbers over 7 days), while the corresponding unadapted parental strains exhibited no growth over the same period.(ABSTRACT TRUNCATED AT 250 WORDS)